Empowering Young Children in Numeracy through Role-Playing Games Application: Advancing Independent Curriculum Goals - Rita Mariyana; Ridha Marissa El Seira; Aditya Aditama Putri Hikmatyar (Jurnal Penelitian Pendidikan IPA, 2025)
Basic numeracy education is crucial for the development of early childhood as a foundation for logical and analytical thinking. This study aims to develop an educational game application based on the Role-Playing Game (RPG) model, designed to effectively enhance basic numeracy comprehension in early childhood. Aligned with the principles of the Independent Curriculum, which emphasizes child-centered, exploratory, and enjoyable learning, the application was developed using the ADDIE model, structured across five stages: Analysis, Design, Development, Implementation, and Evaluation. The results indicate that this RPG game application, which includes narrative elements, interactive characters, and tiered challenges, significantly improves children's numeracy skills, such as number recognition and basic addition. Furthermore, the application enhances learning motivation through positive feedback features. Integrating local cultural elements in the application’s design further enhances its relevance, supporting children in learning within a context that reflects their real-life environment. Consequently, this application is expected to serve as an innovative alternative for effective, interactive numeracy education aligned with the principles of the Independent Curriculum.